The Replanting of a 1.1 from an Ectopic Position during the Course of Orthodontic Therapy: Follow-Up at 8 Years - Michele M. Figliuzzi; Maria Altilia; Simone Altilia; Amerigo Giudice; Leonzio Fortunato (Hindawi Limited, 2019)
The case that is reported here describes the replanting of a 1.1 from an ectopic position during orthodontic therapy. The 9-year-old patient suffered from class 2 type malocclusion with the upper maxilla contracted, right-left posterior cross-bite. The clinical case presented the following details: in the upper incisor group, the 1.1 was overlapping the 1.2 and was distalised and completely vestibularised, whilst in the place of the 1.1, a 1.1 supernumerary persisted in occlusion. Following several medical investigations, such as OPT and, most importantly, TC cone beam investigation, the dangerous position of the dental element became clear. This did not present vestibular cortical bone but only gingival mucosa. Following these investigations, the difficulty in bringing the dental element into its natural position through orthodontic treatment became obvious since the natural position was without sufficient bone support. From this, it became obvious that surgery and replanting of the 1.1 immediately after the extraction of the supernumerary 1.1 was the only choice available.